COVID-19 and Indonesia - Siti Setiati; Muhammad Khifzhon Azwar (Acta Medica Indonesiana)
Coronavirus disease 2019 (COVID-19) pandemic is an ongoing problem in more than 200 countries in the world. Indonesia has been greatly affected by COVID-19 with case fatality rate (CFR) being 8.9% in the end of March 2020. We have some room for improvement related to the unreadingess of healthcare facility and the major steps taken by the government. It is suggested that the country should have stricter Stay-at-Home notice, suppress the spread by imposing lockdown on a large scale, improve healthcare service, and increase the availability of personal protective equipments (PPE). It is important to avoid an epidemic peak that potentially overwhelms healthcare service by quarantining the case contacts. Lockdown may prolong the epidemic doubling time significantly. Demand of health system is likely to grow since the number of COVID-19 case is likely to rise. Effective procedures for protecting medical staff from infection are essential. Scientific research in Indonesia is also crucial to provide suggestion and recommendation pertinent to COVID-19.